Underreporting and Experimental Effects on Work Effort: Evidence from the Gary Income Maintenance Experiment - Greenberg, David; Moffitt, Robert; Friedmann, John (The Review of Economics and Statistics, 1981)
David Greenberg, Robert Moffitt, John Friedmann, Underreporting and Experimental Effects on Work Effort: Evidence from the Gary Income Maintenance Experiment, The Review of Economics and Statistics, Vol. 63, No. 4 (Nov., 1981), pp. 581-589